2014
DOI: 10.1186/cc13721
|View full text |Cite
|
Sign up to set email alerts
|

Utility of thromboelastography and/or thromboelastometry in adults with sepsis: a systematic review

Abstract: IntroductionCoagulation abnormalities are frequent in sepsis. Conventional coagulation assays, however, have several limitations. A surge of interest exists in the use of point-of-care tests to diagnose hypo- and hypercoagulability in sepsis.We performed a systematic review of available literature to establish the value of rotational thromboelastography (TEG) and thromboelastometry (ROTEM) compared with standard coagulation tests to detect hyper- or hypocoagulability in sepsis patients. Furthermore, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
1
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 60 publications
(179 reference statements)
2
131
1
19
Order By: Relevance
“…Viscoelastic coagulation tests measure the dynamics of clot formation from initiation, speed of clot strengthening through to clot stabilisation and dissolution, and give an integrated assessment of the entire coagulation process. It has been demonstrated that they may give more valuable information about the overall haemostatic status than PT/INR in critically ill patients [33] and in patients with liver disease [34].…”
Section: Discussionmentioning
confidence: 99%
“…Viscoelastic coagulation tests measure the dynamics of clot formation from initiation, speed of clot strengthening through to clot stabilisation and dissolution, and give an integrated assessment of the entire coagulation process. It has been demonstrated that they may give more valuable information about the overall haemostatic status than PT/INR in critically ill patients [33] and in patients with liver disease [34].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the quality of evidence supporting thromboelastometry (TEM) in routine sepsis monitoring is low to moderate. [9] In addition, studies using TEM in sepsis to determine proper therapy institution are lacking. Also, definitions for hyper- and hypocoagulation are not standardized and internal validity of their use in clinical trials is often a concern.…”
Section: Measurement Of Coagulation In Sepsismentioning
confidence: 99%
“…These settings include cardiac surgery [6770], liver transplantations [71], sepsis [72], trauma [7379], obstetrics [80], psychophysiological stress [81]. These systems have also been utilized to evaluate anticoagulant activity [82, 83] and determine what the critical threshold value is for the initiation of antifibrinolytic therapy in trauma [84].…”
Section: Thrombin Generation Assaysmentioning
confidence: 99%